Effects of Dance and Movement Therapy (DMT) Versus Progressive Muscle Relaxation (PMR) on Quality of Life among Elderly Residing in Selected Old Age Homes of Haryana: A Quasi Experimental Study (Indian Journal of Public Health Research & Development, 2020)
Elderly age group is a controversial issue as it is a natural process which presents a unique challenge forevery individual in society. Thus it is being considered that quality of life among elderly is poor due toignorance that is the vulnerable population. The objective of the study was to evaluate the quality of lifeamong elderly before and after administration of dance and movement therapy and progressive musclerelaxation. Methodology: Quantitative research approach, quasi experimental non equivalent control grouppretest post test design, with Purposive sampling technique. Data was collected by using Modified WHOQOLBref questionnaire for assessing quality of life. Thus findings of the study showed effectiveness ofdance and movement therapy and progressive muscle relaxation on quality of life as the calculated RepeatedMeasure Anova F value (DMT F=1027.03, p=0.00 and PMRF=496.31, p=0.00).Result also shows in PMRgroup quality of life among elderly was found to be statistically significant with source of income and historyof chronic illness i.e (F=3.534, p =0.02) and (t= 2.922, p=0.00) and in DMT group quality of life amongelderly was found to be statistically significant with nature of previous occupation and history of chronicillness i.e (F=2.935, p=0.05) and (t=2.408, p=0.02). Conclusion: DMT and PMR was effective interventiongiven for 30 minutes at once daily for improving quality of life among elderly.
Keywords: Quality of life, Dance and movement therapy (DMT), Progressive Muscle Relaxation (PMR), Elderly residing at old age homes